La gestión de diseño estratégico aplicado al posicionamiento digital prospectivo de pymes caso de estudio Anpersan - Christian David, Villacis Pantoja (2021)
This work establishes the importance of Design Management applied to the prospective digital positioning of PYMES (Pequeñas y Medianas Empresas) (Small and Medium-sized Companies, in English) where there are several problems since in Ecuador there are 31.8% of adults, who register an economic activity but in most cases these ventures have a lifetime of 3 to 5 years for not complying with the strategic objectives and the absence of a correct direction of the company, for this reason, this research is focused on the creation of a “DPe” strategic management model called “Strategic Prospective Design”. For the development of it, a mixed approach is used since it seeks to extract qualitative and quantitative data, with empirical, bibliographic and analytical methods, techniques and instruments detailed in chapter 3 are used. The main results are the model and validation, as well as the presentation of the “DPe” methodology to be able to accurately develop the model with the tools in each phase, the phases are presented in a toolkit for greater understanding and visualization. It is important to mention that this model is applied in the study case to Anpersan advertising agency.